Uprisings: A meditation on feminist strategies for enacting the common - Oliveira, J.M. (LGBTQ+ intimacies in Southern Europe: Citizenship, care and choice, 2022)
This chapter discusses queer and feminist uprisings as way of creating a politics of the common in the scenario of the bleak perspectives of Capitalocene, neoliberal rationalities governing the economies, with hard-right conservative parties in power in several countries. Starting with the global level, the text first takes a look at feminist organizing against hard right specifically in Brazil, with the #elenao movement. Focusing on regional southern European contexts, the text analyses the Critical Pride movement in Madrid and in Left Bloc political party in Portugal. Tackling recent political and social contexts, the text looks at these two possibilities as way of counteracting (neo)liberal perspectives on identities and politics by creating a common ground with other social movements. This is a project of alliances, an enactment of the common.